Nothing stays buried - Tracy, P. J. (Tracy, P. J. Monkeewrench novel, 2017)
"The Monkeewrench crew returns to face the city of Minneapolis's worst nightmare--a rampant serial killer on the loose--in the electrifying new thriller. When Minneapolis homicide detectives Leo Magozzi and Gino Rolseth are called to a crime scene in a heavily wooded city park, everything about the setting is all too familiar. And when they discover a playing card on the victim's body, their worst fears are confirmed--there's a serial killer operating in the city for the first time in years. Across town, Grace MacBride and her unconventional partners at Monkeewrench Software find themselves at both personal and career crossroads. Weary of the darker side of their computer work for law enforcement, they agree to take on a private missing-persons case in a small farming community in southwestern Minnesota. As the violence accelerates in Minneapolis, Magozzi and Gino soon realize their killer is planning to complete the deck, and they enlist Monkeewrench to help stop the rampage. As a baffling tangle of evidence accumulates, the cops and Monkeewrench make the unlikely connections among a farmer's missing daughter, a serial killer, and a decades-old stabbing that brings them face-to-face with pure evil"--